2003
DOI: 10.1002/jbm.a.10337
|View full text |Cite
|
Sign up to set email alerts
|

Microcapsules made by enzymatically tailored alginate

Abstract: Alginate is widely used for encapsulation of cells. Alginate is a linear block copolymer consisting of mannuronic acid (M) and guluronic acid (G). It has been shown that enzymes known as C-5 epimerases convert M to G in the polymer chain, giving rise to novel alginates with tailored properties. One of these enzymes, AlgE4, converts M blocks into blocks of strictly alternating M and G. In this study we investigated how alginate epimerized by AlgE4 affected capsule properties such as stability and permeability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 31 publications
(41 reference statements)
3
54
0
1
Order By: Relevance
“…20 Also, several studies have shown that introduction and elongation of MG sequences in alginates from brown algae by in vitro epimerization with AlgE4 leads to increased syneresis. 21,22 This is thought to be a consequence of increased elastic segment flexibility 23 and formation of secondary MG/MG junctions through a calcium dependent zipping mechanism. 24 There was a big difference in the syneresis in Ca-limited gels and Ca-saturated gels in this study.…”
Section: Analysis Of Gels Made From Epimerized Materials and The Effementioning
confidence: 99%
“…20 Also, several studies have shown that introduction and elongation of MG sequences in alginates from brown algae by in vitro epimerization with AlgE4 leads to increased syneresis. 21,22 This is thought to be a consequence of increased elastic segment flexibility 23 and formation of secondary MG/MG junctions through a calcium dependent zipping mechanism. 24 There was a big difference in the syneresis in Ca-limited gels and Ca-saturated gels in this study.…”
Section: Analysis Of Gels Made From Epimerized Materials and The Effementioning
confidence: 99%
“…In the present study we have evaluated the CLSM as a tool for investigating the distribution of polymers in alginate-PLL-alginate microcapsules using fluorescent label covalently linked to the polymers or by using a fluorescent cross-linking ion, Tb material, respectively (Pronova LVG, Pronova Biomedical, Oslo, Norway). High molecular weight mannuronan from Pseudomonas aeruginosa (strain 8830) was harvested from culture plates (Ertesvåg and Skjåk-Braek, 1999), epimerized with the recombinant mannuronan C-5 epimerase AlgE4 as described earlier (Strand et al, 2002b). This polyalternating alginate was further degraded slightly by hydrolysis and used as coating alginate.…”
Section: Introductionmentioning
confidence: 99%
“…Microbeads are one-component systems commonly made of alginate cross-linked with divalent cations [21,22]. Microcapsules are composed of two or more polymers forming complexes reducing the permeability.…”
Section: Microspheresmentioning
confidence: 99%
“…Microcapsules are composed of two or more polymers forming complexes reducing the permeability. Commonly polycations like poly-L-lysine (PLL), poly-L-ornithine (PLO), poly-D-lysine (PDL), chitosan or poly-methylene-co-guanidine (PMCG) are being applied [22][23][24][25][26]. In addition, some protocols include the solubilizing of the inner core.…”
Section: Microspheresmentioning
confidence: 99%
See 1 more Smart Citation